2016
DOI: 10.1097/md.0000000000003380
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anthocyanins on Blood Pressure

Abstract: The findings of clinical studies concerning the association between anthocyanins supplementation and blood pressure (BP) are inconsistent.In order to provide a more precise estimate of the overall effect of anthocyanins on systolic blood pressure (SBP) and diastolic blood pressure (DBP), we conducted a meta-analysis of clinical trials about anthocyanins supplementation and BP.PubMed, Web of Science, Wanfang Database, and China National Knowledge Infrastructure (CNKI) (until October 2015) were searched to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
(36 reference statements)
1
11
1
Order By: Relevance
“…Similar lowering effects on BP were reported with pomegranate juice (−4.96/−2.01 mmHg, SBP/DBP) [ 53 ]. On the other hand, grape (poly)phenols, green tea and cocoa had smaller effects on blood pressure than the present meta-analysis (−1.54/non-significant mmHg for grape seed extract [ 54 ]; −1.98/−1.92 mm Hg for green tea [ 55 ]; and non-significant/−1.60 mmHg for cocoa [ 56 ], SBP/DBP), and anthocyanins had no significant effects on blood pressure [ 57 ]. On blood lipids, no significant effects were reported for pomegranate juice and grape seed extract meta-analyses [ 54 , 58 ].…”
Section: Discussionmentioning
confidence: 82%
“…Similar lowering effects on BP were reported with pomegranate juice (−4.96/−2.01 mmHg, SBP/DBP) [ 53 ]. On the other hand, grape (poly)phenols, green tea and cocoa had smaller effects on blood pressure than the present meta-analysis (−1.54/non-significant mmHg for grape seed extract [ 54 ]; −1.98/−1.92 mm Hg for green tea [ 55 ]; and non-significant/−1.60 mmHg for cocoa [ 56 ], SBP/DBP), and anthocyanins had no significant effects on blood pressure [ 57 ]. On blood lipids, no significant effects were reported for pomegranate juice and grape seed extract meta-analyses [ 54 , 58 ].…”
Section: Discussionmentioning
confidence: 82%
“…Also, the effects of tree nuts were shown to reduce T-C, LDL-Cand TAGs [23]. Regarding the ANC-containing products, a previous meta-analysis looking at the supplementation with blueberries and their effect on blood pressure concluded that the results were not convincing and that more RCTs were needed [19]. In the current meta-analysis, ANC-containing products have come out as quite consistent regulators of SBP and DBP.…”
Section: Discussionmentioning
confidence: 87%
“…Previous reviews and meta-analyses of randomized-controlled trials (RCTs) have explored the evidence of the effects of the intake of berry [16,17,18,19,20,21], nut [22,23], pomegranate [24,25], and grape [26,27] foods and (or) derived products on different cardiometabolic risk factors (i.e., serum lipids, blood pressure, glucose). The results of these analyses have indicated inconsistencies in the overall effects and have pointed at potential different responses between different subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, meta-analysis of clinical trials on polyphenol supplementation showed contrasting results. A previous meta-analysis of randomized controlled trials on the effects of anthocyanins on blood pressure showed overall null results [65]. Other meta-analyses on soy isoflavones supplementation reported that soy isoflavone extracts significantly decreased systolic but not diastolic blood pressure in adult humans, and no dose–response relationship was observed [66], while another meta-analysis suggested that the effects were more evident in hypertensive, but not in normotensive individuals [67].…”
Section: Discussionmentioning
confidence: 99%